Nanotechnology-enabled energy efficiency in semiconductors: plasmon-induced super-semiconductors and ballistic transport devices - Li, Zhigang; Wei, Bingqing (Frontiers in Nanotechnology, 2025)
The semiconductor industry consumes staggering amounts of electricity annually, surpassing the energy usage of over 100 nations. This immense consumption not only underscores the environmental impact but also generates substantial heat within semiconductor devices, adversely affecting their performance, lifespan, and reliability, posing significant challenges to the advancement of nanodevices. To address these challenges, reducing energy consumption through the use of advanced, energy-efficient technologies has become a priority. Energy-efficient electronics (EEE), enabled by nanotechnology, have the potential to drastically reduce energy consumption in semiconductor devices while simultaneously enhancing their performance. From this perspective, this discussion focuses on two nano-semiconductor technologies poised to advance EEEs: plasmon-induced metal-based semiconductors and ballistic transport in nanostructured semiconductors. For example, p-n junction diodes constructed with the metal-based semiconductors can reduce power consumption by 3-4 orders of magnitude compared with silicon-based devices due to their low resistivity; similarly, the excellent ballistic transport property of InSe FETs enables an energy-delay product of ∼4.32*10−29 Js/μm of the devices, one order of magnitude lower than the Si counterparts. This perspective examines the offerings of each of these disciplines and explores how nanotechnology can be utilized to conserve energy and enhance performance. Differences from traditional technologies and limitations in existing research will also be assessed.